2021
DOI: 10.1108/gm-06-2020-0174
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in corporate boardrooms and risk disclosure: Indian evidence

Abstract: Purpose The study aims to pervade the gap in the domain of risk disclosure and gender diversity, which is comparatively uncharted. Gender diversity being a crucial element of corporate governance can deepen understanding on the issue in the backdrop of a developing country such as India, so this study aims to investigate the relationship between gender diversity on board and corporate risk disclosure. Design/methodology/approach Four measures of gender diversity, i.e. BLAU index, SHANNON index, proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…Likewise, board independence positively influences RD (Abraham and Cox, 2007; Khandelwal et al , 2020), whilst Saggar and Singh (2017) and Ibrahim et al (2019) found no association. Also, board gender diversity positively influences RD (Ntim et al , 2013; Saggar et al , 2021), whilst Allini et al (2014) found a negative association.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Likewise, board independence positively influences RD (Abraham and Cox, 2007; Khandelwal et al , 2020), whilst Saggar and Singh (2017) and Ibrahim et al (2019) found no association. Also, board gender diversity positively influences RD (Ntim et al , 2013; Saggar et al , 2021), whilst Allini et al (2014) found a negative association.…”
Section: Introductionmentioning
confidence: 92%
“…Further, women are inquisitive by nature which makes them better at influencing corporate outcomes than their male counterparts (Carter et al, 2003). Empirically, the majority of studies found that board gender diversity positively influences RD (Kılıc ¸and Kuzey, 2018;Salem et al, 2019;Bufarwa et al, 2020;Khandelwal et al, 2020;Saggar et al, 2021), whereas Allini et al (2014) found a negative association. In Kenya, the CMA Code of Corporate Governance does not set any specific diversity target for listed companies.…”
Section: Board Gender Diversitymentioning
confidence: 99%
See 3 more Smart Citations